RITUXIMAB DELAYS WOUND HEALING AND DECREASES WHITE BLOOD CELL COUNT IN MALE MICE - SELMAN, SELMAN M; Bashara, Majid K; Raji, Ahmed; Kadhum, Ouday H (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The aims of this research are to evaluate the effect of rituximab on wound healing, some hematological parameters, histological changes in wound healing, and histopathological changes in some organs in male mice. Methods: Totally, 15 adult male mice (25-30 g) were enrolled in this study. Animals were kept in the animal house College of Medicine/University of Babylon, and the temperature was controlled on 25Â°C and 14 hrs light and 10 hrs dark cycles. The animals were provided with standard diet and water ad libitum. The animals were divided randomly into 3 groups, five mice in each group, Group 1 (control group) received no treatment, Group 2 received rituximab 1 m/kg, IP, at days 0, 5, and 10 after wounding, in Group 3, rituximab was topically applied to the wound at days 0, 5, and 10 after wounding. Results: The results yield that the wound healing significantly decreased (p<0.05) in Groups 2 and 3 as compared to control group. While the results regarding white blood cells (WBCs) count, there is a significant decrease in WBC count in Group 2 (p>0.05). Platelets and red blood cell count in significantly increased in Group 3 as compared to control group (p<0.05). There were no histopathological changes in the skin, kidneys, and spleen. In liver, nonsignificant histopathological changes (p>0.05) found in Group 2 and 3 as compared to control group. Conclusion: Rituximab delays wound healing and reduces WBC count in male mice. Keywords: Rituximab, Wound healing, Lymphocyte, CD20, White blood cells, Mice.